Wind forces on circular steel tubular lattice structures with inclined leg members. (15th December 2017) - Li, Yan; Li, Zhengliang; Yan, Bowen; Yan, Zhitao
Highlights: A new type of rigid model for the wind tunnel tests and the "member subtraction method" is proposed herein by sequentially removing the accessory members of the lattice truss until remaining leg members. The effects resulting from individual horizontal and diagonal bars and leg members on the overall drag forces of lattice structures were studied. The aerodynamic interference between diagonal and leg members was tested in the experimental investigation by using the three-cylinder model. Abstract: The wind forces on the steel lattice structures have drawn increasing concerns in the structural design of high-rise and long-span buildings and structures due to their low damping, light self-weight, and high flexibility. The aim of this paper is to assess the aerodynamic forces on circular steel tubular lattice structures with vertical and inclined leg members using the wind tunnel tests. In order to elucidate the underlying mechanism of wind loads contributed by the individual members of lattice structures, a new type of rigid experimental model for High-frequency force balance (HFFB) wind tunnel tests is proposed in the study. And the individual member of lattice structures can be sequentially removed until remaining vertical or inclined leg members, which is referred to as "member subtraction". The experimental results reveal that with the same solidity ratio, the drag coefficient of lattice structure with inclined leg members is approximately 9% smaller than that with vertical ones. This indicates that the configuration of steel lattice structures, such as inclined leg members, might exert indispensable effects on the drag forces, which has yet been considered in the current wind codes and standards. In addtion, in order to clarify the interference mechanism between the leg and diagonal members, the wind tunnel tests of a three-cylinder model are performed and the wind tunnel results indicate that the presence of diagonal members in lattice structures would increase the overall drag coefficients in the scenario of small separation distances. Finally, the advantages and disadvantages of structural configuration (with and without horizontal or diagonal members) and their implications on structural design are discussed.